A quality assessment tool for improvement planning. (18th May 2009) - Woolford, Sam
The identification and prioritisation of improvement opportunities can be a challenge for many organisations due to a variety of resource limitations. This can result in improvement efforts that do not have a clearly defined linkage to the return that they will generate or to the achievement of key organisation strategies intended to maintain or advance the organisation's competitive position. The current research proposes the development of a decision support tool, based on the analytic hierarchy process and a self-assessment tool for evaluating current performance, which can effectively and efficiently identify and prioritise improvement opportunities for annual improvement planning. The decision support tool can be easily automated to facilitate implementation.